Alfonso de Palencia : travaux en cours et perspectives - Alice Carette (Atalaya)
The work of the humanist Alfonso de Palencia, recognized by the Hispanic medievalists for its historical and cultural value, is still under-exploited, mainly because of the incomplete nature of its editing and diffusions. However, it has been the subject of a new research dynamic for several years. The seminar Alfonso de Palencia: travaux en cours et perspectives, organized in the ENS of Lyon on june, 9th and 10th 2016, was intended to be part of the renewal of the works devoted to the historian. This text offers a synthetic presentation of the file constituted by the five contributions, which are derived from it. Their authors, Susanna Allés Torrent, Francisco Bautista, Alice Carette, Matías Ferrera et Jeremy Lawrance propose new philological and editorial approaches to Palencia’s work.